2012
DOI: 10.2106/jbjs.k.01257
|View full text |Cite
|
Sign up to set email alerts
|

Patellar Resurfacing in Primary Total Knee Replacement

Abstract: Patients who underwent patellar resurfacing experienced anterior knee pain and satisfaction with the arthroplasty procedure that were equivalent to those experienced by patients whose patella was not resurfaced; however, these patients underwent significantly fewer additional surgical procedures. Further long-term follow-up of modern prostheses in randomized studies measuring outcome with a patella-specific score is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
86
3
10

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(107 citation statements)
references
References 1 publication
6
86
3
10
Order By: Relevance
“…Beaupre et al [43] in 2012, performed a randomized controlled trial, with a follow-up of 5-10 years, in which they agreed that patellar resurfacing showed no difference with non-resurfacing regarding knee specific outcomes, like pain, stiffness, and function. Also in 2012, Pilling et al [44] in a meta-analysis of randomized controlled trials, highlighted the advantages of this method in the field of preventing additional surgical procedures and patella-femoral complications, but, nevertheless, reported no difference in operative time, infection rate, radiographic appearance, patient satisfaction, and anterior knee pain.…”
Section: No Differences Among Studied Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…Beaupre et al [43] in 2012, performed a randomized controlled trial, with a follow-up of 5-10 years, in which they agreed that patellar resurfacing showed no difference with non-resurfacing regarding knee specific outcomes, like pain, stiffness, and function. Also in 2012, Pilling et al [44] in a meta-analysis of randomized controlled trials, highlighted the advantages of this method in the field of preventing additional surgical procedures and patella-femoral complications, but, nevertheless, reported no difference in operative time, infection rate, radiographic appearance, patient satisfaction, and anterior knee pain.…”
Section: No Differences Among Studied Groupsmentioning
confidence: 99%
“…No difference between the 2 groups in terms of anterior knee pain, knee pain score, Knee Society score and knee function score Pilling et al [44] Meta-analysis of randomized controlled trials. Patellar resurfacing vs nonresurfacing in primary TKR…”
Section: Ref Type Of Study Outcomementioning
confidence: 99%
“…Abdel et al reported that at fifteen years the non-posterior-stabilized knee replacements performed slightly better in the knees with deformities than in those without deformities and that the opposite was true for posterior-stabilized knee replacements, which performed better in the knees without deformities 11 . The role of patellar resurfacing in total knee arthroplasty has been investigated, often with contradictory results [27][28][29][30][31][32] . The results of our study indicate that the revision risk for posteriorstabilized knees is double that for non-posterior-stabilized knees in cases with nonresurfaced patellas.…”
mentioning
confidence: 99%
“…Some registries contained relatively few posterior-stabilized procedures. Significant differences in the rates of patellar resurfacing existed between registries and had a major effect on survival [29][30][31][32] . Some registries within the group are larger than others, with different follow-up intervals, and therefore might have had a greater influence on the results.…”
mentioning
confidence: 99%
“…Despite its success, many patients remain dissatisfied after TKA, where patellofemoral pain and instability remain among the most common reasons for reoperation or revision (3)(4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%